Electrical Studies of Fe2O3 Nanocrystal Using Nanogap Electrodes Prepared by Electrochemical Method - Dong, Xiaodong; Liu, Junhua (Asian Journal of Chemistry, 2013)
The gold nanogap electrodes were successfully fabricated with a two-step electrochemical method in solution by a home-made electrochemically controlled system. By careful controlling the etching/deposition process, stepwise conductance behaviour could be clearly observed. The formed gold nanogap electrodes were used to study the electrical properties of single Fe2O3 nanocrystal. The current-voltage characteristics of these devices exhibited a Coulomb staircase at room temperature. This work is possible to be adapted to the study of a host of nanocrystals made by solution chemistry and is of great significance for molecular and nano electronics.